Post-Independence NU Dynamics Towards the Establishment of the NU Outline as a Decision of the Situbondo Congress 1945-1984 - Fawaid, Ikmal (El Tarikh : Journal of History, Culture and Islamic Civilization, 2022)
After Indonesian independence in 1945, NU began to be actively involved in practical politics. Its practical political role is channeled through the Masjumi Party, the NU Party, and PPP. Within these three political forums, NU experienced various dynamics which made NU finally decide to withdraw from practical politics. Apart from that, there was also influence from the Old Order and New Order governments which also triggered and encouraged the process of his withdrawal. All of this is part of the social process of the discourse of Khittah NU which emerged from 1959 until it was determined to be the decision of the 1984 Situbondo Muktamar. How was the development of the discourse on the Basic Strategies of NU 1959-1984? Why was the Khittah NU determined as the decision of the 1984 Situbondo Congress? Furthermore, as a study of the past, this study uses historical research methods which have 5 stages in the form of topic selection, source gathering, verification, interpretation, and writing. In addition, this study uses a sociological approach to capture the social dimension of every phenomenon found and uses social process theory to carry out analysis and synthesis. To provide a corridor in writing, the central circle model is used because it is considered relevant to research. The conclusion of this study shows that NU experiences all forms of social processes. Cooperation, competition, conflict and conflict, as well as accommodation have been experienced by NU as a social reality that must be faced together with various other groups. In its relationship with one party, NU does not only cooperate, sometimes NU has to compete and even fight with the group where various decisions are taken by bearing some risks while continuing to try to achieve wider benefits.